A NEW FIND OF CROESEID COINS FROM SARDIS. - Cahill, Nicholas; Bruce, William; Kroll, John H.; Frank, Emily B.; Kim, Jennifer; Castriota, Brian; Grant, Ameya; Şimşek, H. Süheyla; Güngör, İzel; Erdal, Yılmaz Selim (Hesperia)
Nine silver croeseids were discovered at Sardis, together with bones of their owner, in the historic destruction level of 547 bce, when Cyrus defeated Croesus. All nine are heavily worn, the result of more than 14 years of circulation. This supports Robert Wallace's argument that Croesus's reign began in the 580s rather than in 561 bce. The most significant achievement of Croesus's monetary reform was the introduction of coinage in pure silver, which enhanced the convenience of small change and was quickly adopted throughout the Greek world. Meticulous conservation of the nine croeseids allowed use wear to be distinguished from postdeposition corrosion. The discovery offers new insights into the origins of the world's first silver coins.